PENGARUH RISIKO BISNIS, UKURAN PERUSAHAAN, KEPUTUSAN INVESTASI, BOARD SIZE, DAN AUDIT COMMITTEE TERHADAP STRUKTUR MODAL DI PERUSAHAAN PERTAMBANGAN - Bella Bella; Hendro lukman (Jurnal Paradigma Akuntansi, 2022)
This study aims to obtain empirical evidence regarding the effect of business risk, company size, investment decisions, board size, and audit committee on the capital structure of mining companies listed on the Indonesia Stock Exchange in 2016-2019. The data used in this study are secondary data. The sample used in this study was 76 mining company data and the technique used was purposive sampling. This mining company data processing uses SPSS (Statistical Product and Service Solution) version 23 program.The results of this study indicate that business risk has a significant effect on capital structure, while company size, investment decisions, board size, and audit committee do not have a significant effect on the structure. capital. The implication of this research is that management needs to reduce the company's business risk so that the capital structure remains good.